OHP-015 Clinical Research in France and Quebec. (12th March 2013) - Guérin, A; Tanguay, C; Lebel, D; Bourdon, O; Bussières, JF
Abstract : Background: Pharmacy practise is evolving in most countries. Hospital pharmacists are pivotal in the organisation and the support of clinical trials. We looked at the current state of pharmacy practise in clinical research. Purpose: To identify differences in clinical research organisation and pharmacy practise between France and Quebec (Canada). Materials and Methods: This is a descriptive study. A literature review was performed in order to describe the organisation of clinical research and the role of pharmacists in clinical research for both countries. Differences were identified by a panel consisting of one French pharmacy intern, one French hospital pharma cist, one Quebec research assistant and two Quebec hospital pharmacists. Results: Fourteen differences relating to research organisation were identified. France and Canada have different normative frameworks, regulatory authorities, authorization processes, delays and shutdown processes. While it is encouraged, clinical trial registration is not mandatory in Canada. Data needs to be archived for 15 years in France vs. 25 years in Canada. Institutional review boards (IRB) have different names, location, composition, nomination processes, mandate duration and informed consent processes for minors. Seven key differences in pharmacy practise were identified. There are different authorization processes for drug compounding and manufacturing. Pharmacy fees are based on a national reference in France, but not in Canada. Software for the computerization of pharmacy services for clinical trials is common in France. In addition to drug trials, French pharmacists also manage sterile medical devices and medicinal products derived from human blood. Canadian pharmacists offer decentralised pharmaceutical care to hospitalised patients. Canadian pharmacists can be principal investigators if a doctor is the qualified investigator. Conclusions: Clinical research organisation is similar on many aspects, but 21 main differences were identified. Comparisons between countries help identify best practise and may contribute to practise improvement. No conflict of interest.